The studies on structure and properties of organic-inorganic nanohybrid material from epoxidized natural rubber (ENR-50) and titanium dioxide (Ti02) - Dahham, Omar Sabbar (Faculty of Engineering Technology, 2018)
The main objective of this work is to synthesize a new hybrid from Epoxidized Natural Rubber (ENR-50) and Titanium dioxide (TiO2) using sol-gel technique. Furthermore, this work aims to understand the structure of this prepared hybrid as well as to evaluate its potential uses in optical applications. This objective is accomplished through the following objectives; to synthesize and characterize a new organic/inorganic hybrid from ENR-50 and Titania precursors using a wide range of analyses (FTIR, X-RD, TGA, DSC, SEM-EDX, TEM, AFM, UV-Vis, and Refractivity Index) and then evaluate the possibility of using this hybrid in the optical applications